Efficacy of a hybrid take home and in class summative assessment for the postsecondary physics classroom - Stonaha, Paul; Douglas, Stephanie T (Physics education, 2024)
Assigning course grades to students requires obtaining accurate measures of the students’ understanding and knowledge of the topic. The induced stress from a traditional summative assessment is known to negatively impact student grades, confounding the connection between knowledge and test grades. Documented approaches to reduce stress during examinations can lead to a distracting testing environment (two-stage tests) or are subject to cheating (take-home tests). We have developed a hybrid take-home/in-class exam that avoids such difficulties. We present herein the responses from student surveys conducted after each exam. The results of the surveys indicate that the hybrid exam method reduces test anxiety while improving students’ self-reported mastery of physics, as compared to traditional in-class summative assessments. These findings are significant at the p < 0.05 level. Lastly, we discuss the difficulties encountered in applying this test approach.